Knockout of apolipoprotein A‐I decreases parenchymal and vascular β‐amyloid pathology in the Tg2576 mouse model of Alzheimer's disease. (14th May 2019) - Contu, L.; Carare, R. O.; Hawkes, C. A.
Abstract : Aims: Apolipoprotein A‐I (apoA‐I), the principal apolipoprotein associated with high‐density lipoproteins in the periphery, is also found at high concentrations in the cerebrospinal fluid. Previous studies have reported either no impact or vascular‐specific effects of apoA‐I knockout (KO) on β‐amyloid (Aβ) pathology. However, the putative mechanism(s) by which apoA‐I may influence Aβ deposition is unknown. Methods: We evaluated the effect of apoA‐I deletion on Aβ pathology, Aβ production and clearance from the brain in the Tg2576 mouse model of Alzheimer's disease (AD). Results: Contrary to previous reports, deletion of the APOA1 gene significantly reduced concentrations of insoluble Aβ40 and Aβ42 and reduced plaque load in both the parenchyma and blood vessels of apoA‐I KO × Tg2576 mice compared to Tg2576 animals. This was not due to decreased Aβ production or alterations in Aβ species. Levels of soluble clusterin/apoJ were significantly higher in neurons of apoA‐I KO mice compared to both wildtype (WT) and apoA‐I KO × Tg2576 mice. In addition, clearance of Aβ along intramural periarterial drainage pathways was significantly higher in apoA‐I KO mice compared to WT animals. Conclusion: These data suggest that deletion of apoA‐I is associated with increased clearance of Aβ and reduced parenchymal and vascular Aβ pathology in the Tg2576 model. These results suggest that peripheral dyslipidaemia can modulate the expression of apolipoproteins in the brain and may influence Aβ clearance and aggregation in AD.